Regularity of Jacobians by subdeterminants - Anna Verde (Journal of Function Spaces and Applications)
Some regularity results for the Jacobian determinant Ju of a mapping u∈W1,  n-1(Ω, Rn), having the cofactor matrix of Du in Ln/n-1(Ω), in Hardy-Orlicz spaces are given.